Respostas

2014-08-01T20:23:21-03:00
X² -2x = 2x - 4
Igualamos a equação a 0

x² -2x -2x +4
x² -4x +4 = 0
Agora aplica-se a fórmula de Bhaskara

x = -b+-√b²-4.a.c
            2a
x = -(-4)+-√-4².-4,1.4
              2.1
x= 4 +-√0
         2
x = 4+-0
        2
x' = 4+0
        2
x' = 2
x" = 4-0
        2
x" = 2
2014-08-01T20:25:52-03:00
X²- 2x=2x -4
x²-2x-2x-4=0
x²-4x+4=0

a=1
b= -4
c= 4

Δ=b²-4ac
Δ= (-4)² - 4*1*4
Δ= 16-16
Δ= 0


x= -b +- √Δ /2a
x= -(-4) +- √0 / 2*1
x= 4 +- 0 /2


x'= 4+0/2
x'= 4/2
x'= 2


x''= 4 - 0/2
x''= 4/2
x''= 2

Creio que seja isto.
Espero ter ajudado ! Boa sorte !